2011
DOI: 10.1021/jp2051307
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Dependent Ultrafast Photoisomerization Dynamics in Azo Dye

Abstract: Azoaromatic dyes have been extensively investigated over the past decade due to their potential use in a variety of optical devices that exploit their ultrafast photoisomerization processes. Among the azoaromatic dyes, Disperse Red 19 is a commercially available azobenzene nonlinear optical chromophore with a relatively high ground-state dipole moment. In the present study, we used ultrafast time-resolved spectroscopy to clarify the dynamics of a push-pull substituted azobenzene dye. Solution and film samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…If non-degradable organic pollutants in the wastewater are discharged into water, the pollutants will consume the dissolved oxygen in the water. [7][8][9] This will destroy the ecological balance of the water body and cause serious threat to the survival of sh and other aquatic organisms. 10,11 Many studies have reported traditional and advanced methods, such as biological and chemical methods involving electrochemical methods and advanced oxidation processes (AOPs), for the removal of dyes in water.…”
Section: Introductionmentioning
confidence: 99%
“…If non-degradable organic pollutants in the wastewater are discharged into water, the pollutants will consume the dissolved oxygen in the water. [7][8][9] This will destroy the ecological balance of the water body and cause serious threat to the survival of sh and other aquatic organisms. 10,11 Many studies have reported traditional and advanced methods, such as biological and chemical methods involving electrochemical methods and advanced oxidation processes (AOPs), for the removal of dyes in water.…”
Section: Introductionmentioning
confidence: 99%
“…7,[14][15][16][17][18][19] DR1 is of particular practical interest because of its hydroxy group, which can be employed as a covalent linker, for example by functionalizing it with a methacrylate group for embedding in a polybutylmethacrylate (PBMA) matrix. 20 In contrast to plain AB, where the photoisomerisation mechanism is well studied, [21][22][23][24][25][26][27][28][29][30][31] the molecular dynamics of DR1 and related push-pull substituted ABs following excitation in the strong visible ππ*-type absorption band still remains controversial, despite several spectroscopic 32,33 and time-resolved 10,11,34,35 experimental studies and theoretical calculations. 11,[36][37][38][39] This includes the question of the energetic ordering of the first nπ* and ππ* electronic states of the molecules and their distinctive roles in the photoisomerisation and electronic deactivation processes.…”
Section: Introductionmentioning
confidence: 99%
“…The real-time vibrational spectroscopy has successfully resolved the vibrational structure "during" isomerization, and found that the reaction takes place with the two coupled modes of rotation and inversion through the lowest-potential barrier passage on the potential "hyper"-surface. 66) Various studies can be performed utilizing realtime-resolved vibronic and vibrational spectra in many systems. 47)-89) They include such systems as photobiological processes in vision and relevant biopolymers, 60),68) chlorophyll, 67) heme protein, 64) RNA bases, 78) artificial photosynthetic systems.…”
Section: Experimental Setup Of Nopamentioning
confidence: 99%
“…We found that the stability mechanism is due to the reversible photoconversion of trans -azobenzene to cis form resulting not in an irreversible chemical reaction of any kind of photo-degradation or photothermal degradation but in photoenergy dissipation simply to heat. 66 ) There was an argument concerning two candidate mechanisms of the trans-cis isomerization pathways from theoretical viewpoints. One is rotation around the N=N bond and the other is the “inversion” like the umbrella motion in an ammonia (NH 3 ) molecule, which is a quantum mechanical tunneling process.…”
Section: Ultrafast Pump-probe Experimentsmentioning
confidence: 99%
See 1 more Smart Citation